Morphological decomposition of TNG50 galaxies: methodology and catalogue - Zana, Tommaso; Lupi, Alessandro; Bonetti, Matteo; Dotti, Massimo; Rosas-Guevara, Yetli; Izquierdo-Villalba, David; Bonoli, Silvia; Hernquist, Lars; Nelson, Dylan (Monthly notices of the Royal Astronomical Society, 2022)
We present mordor (MORphological DecOmposeR), a new algorithm for structural decomposition of simulated galaxies based on stellar kinematics. The code measures the properties of up to five structural components (a thin/cold and a thick/warm disc, a classical and a secular bulge, and a spherical stellar halo), and determines the properties of a stellar bar (if present). A comparison with other algorithms presented in the literature yields overall good agreement, with mordor displaying a higher flexibility in correctly decomposing systems and identifying bars in crowded environments (e.g. with ongoing fly-bys, often observable in cosmological simulations). We use mordor to analyse galaxies in the TNG50 simulation and find the following: (i) the thick disc component undergoes the strongest evolution in the binding energy-circularity plane, as expected when disc galaxies decrease their turbulent-rotational support with cosmic time; (ii) smaller galaxies (with stellar mass, $10^{9} \lesssim M_{*}/~\rm M_{\odot }\le 5 × 10^{9}$) undergo a major growth in their disc components after z ∼ 1, whereas (iii) the most massive galaxies
Gesehen am 06.09.2022